The Effect of Coconut Shell Mix as a Coarse Aggregate Substitute on Concrete Compressive Strength - Yazid, Muhammad; Puspa Ningrum; Ahmad Kurnain; Tony Hartono Bagio; Sihol Marudut Tua Sinaga (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
Coconut shell waste is one type of agricultural waste that is often underutilized, despite its potential as an alternative material in concrete construction. This study aims to examine the effect of using coconut shells as coarse aggregate in concrete, focusing on the compressive strength of the concrete. Standard concrete with varying coconut shell proportions of 0%, 2%, 4%, 6%, and 8% was tested to observe differences in compressive strength. The results showed that as the percentage of coconut shell in the concrete mix increased, the compressive strength tended to decrease. Concrete with coconut shell proportions of 2%, 4%, 6%, and 8% exhibited average compressive strengths of 16.416 MPa, 16.327 MPa, 14.817 MPa, and 13.779 MPa, respectively, compared to normal concrete with an average compressive strength of 20.008 MPa. This decrease in compressive strength is attributed to the physical properties of coconut shells, which have lower density compared to conventional aggregates. Nevertheless, the use of coconut shells as coarse aggregate offers environmental and economic benefits, such as reducing waste and dependence on limited natural resources.